ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI EDUKASI BREASTFEEDING UNTUK MENINGKATKAN PENGETAHUAN PADA IBU POSTPARTUM TERHADAP SELF EFFICACY DI RS BHAYANGKARA TK.I R SAID SUKANTO - Siti Nur Khasanah (2023)
Postpartum is a condition in which the mother's psychology experiences changes, especially anxiety and stress that can pose a risk of depression. Breastfeeding can improve the health of mothers and babies and one of them is to prevent anxiety in mothers. One of the causes of failure in breastfeeding is the mother's low self-confidence. The purpose of making this scientific work is to analyze nursing care with educationbreastfeeding toself efficacy in postpartum mothers with the BSES-SF measuring instrument.Breastfeeding Self Efficacy Scale Short Form (BSES-SF) to measure the level of confidence of mothers in breastfeeding which consists of 14 question items that have been simplified and become the short version of BSES. The results of the evaluation of the two patients found that the mother's self-efficacy increased with the provision of educationbreastfeeding to primipara postpartum mothers at Bhayangkara TK I R Said Sukanto Hospital. This booklet media can be used as a medium for implementing education and counseling for the community